Respostas
respondido por:
31
Olá,
d(A,B) = √(x-x₀)²+(y-y₀)² = √(3-x)²+(1-4)²
d(A,B) = √(3-x)²+(-3)² = √10
(3-x)²+(-3)² = 10
(3)²+2(3)(-x)+(-x)²+(-3)² = 10
9-6x+x²+9 = 10
x²-6x+18 = 10
x²-6x+18-10 = 0
x²-6x+8 = 0 sendo a = 1, b = -6 e c = 8
Δ = b²-4ac = (-6)²-4(1)(8) = 36-32 = 4
x₁ = (-b+√Δ)/2a = (-(-6)+√4)/2(1) = (6+2)/2 = 8/2 = 4
x₂ = (-b-√Δ)/2a = (-(-6)-√4)/2(1) = (6-2)/2 = 4/2 = 2
Resposta:
O x pode assumir dois valores: x = 2 ou x = 4
d(A,B) = √(x-x₀)²+(y-y₀)² = √(3-x)²+(1-4)²
d(A,B) = √(3-x)²+(-3)² = √10
(3-x)²+(-3)² = 10
(3)²+2(3)(-x)+(-x)²+(-3)² = 10
9-6x+x²+9 = 10
x²-6x+18 = 10
x²-6x+18-10 = 0
x²-6x+8 = 0 sendo a = 1, b = -6 e c = 8
Δ = b²-4ac = (-6)²-4(1)(8) = 36-32 = 4
x₁ = (-b+√Δ)/2a = (-(-6)+√4)/2(1) = (6+2)/2 = 8/2 = 4
x₂ = (-b-√Δ)/2a = (-(-6)-√4)/2(1) = (6-2)/2 = 4/2 = 2
Resposta:
O x pode assumir dois valores: x = 2 ou x = 4
Perguntas similares
9 anos atrás
9 anos atrás
9 anos atrás